ETHICAL MECHANISMS FOR REDUCING CORRUPTION IN THE PUBLIC ETHOSPHERE (TAMADDUN NURI JURNALI, 2024)
The issue of reducing the level of corruption in society is complex and multifaceted, and it cannot be resolved solely through economic or legal approaches. The development of ethical mechanisms plays a crucial role in combating corruption, as these mechanisms involve strengthening the moral values and normative foundations of society.